Clinical and Pathological Findings of Necrotizing Meningoencephalitis in a Maltese Dog - Couto , Rodrigo M.; França , Silvia A.; Rios , Marina A.; Rosado , Isabel R.; Costa , Paula M.; Ecco, Roselene (Brazilian Journal of Veterinary Pathology, 2013)
A 2-year-old, intact female Maltese dog was presented to the veterinarian with a history of acute neurological signs. On neurological examination the dog showed deficit of mental status (apathy and depression), seizures, constant howling, head turn and compulsive circling to the right side and falls to the left side. The treatment protocol using prednisolone (for seizures remission) and cyclosporine (initiated in the chronic stage) did not stop the progression of the disease and euthanasia was elected 65 days later. Necropsy revealed mild cerebral asymmetry, and in the frontal (more affected) parietal and occipital lobes of the right hemisphere there were friable, depressed and yellowish areas characterizing malacia. The left contralateral frontal lobe was edematous and slightly yellowish. At histopathology, the lesions were characterized by marked, multifocal to coalescing necrotizing meningoencephalitis, characterized by focally extensive areas of malacia, especially in the cortex of the frontal and right parietal lobes. Extension of lesions to white matter was observed only in the caudal region of the right frontal lobe. Plasma cells and lymphocytes infiltration was observed around vessels, leptomeninges and in the neuroparenchyma. In addition, the non-cavitation areas were also characterized by neuropil vacuolization, neuronal necrosis, neuronophagia, astroglyosis with various gemistocytes, endothelial hyperplasia and hypertrophy. The immunohistochemical analysis showed predominance of CD3 positive T lymphocytes in proportion to CD79 positive cells. Clinical signs, character and distribution of neurological lesions were compatible with necrotizing meningoencephalitis (NME). This condition, initially reported only in Pugs, currently affects other breeds and attention should be given to the differential diagnosis with other neuropathies in dogs.